Answer:
B
Step-by-step explanation:
x is the value of x which you input into the function and f(x) is the actual function and therefore the output. so when x=3, f(x)= -2. f(3)=-2
3c/5-1/2=-31/2 Add 1/2 both sides
+1/2 +1/2
3c/5=-30/2 Then simplify the fraction
(5)3c/5=-15(5) Multiply 5 both sides
3c=75 Finally, divide by 3 both sides
c=25
So the answer to your question is E.
11 1/5 = (11*5+1)/5=56/5
2 3/4= (2*4+3)/4=11/4
11 1/5 : 2 3/4=56/5:11/4=56/5*4/11=(56*4)/(5*11)=224/55≈4.07≈4
Answer is 4
Answer:
y=3x+4
Step-by-step explanation:
y-y1=m(x-x1)
y-4=3(x-0)
y-4=3x
y=3x+4